The Use of Natural Leaf-Based Media to Improve Classification Ability in Children Aged 5-6 Years in the Integrated Paud Pelangi Saran Belimbing District Melawi Regency - Marlini, Susana (Zona Education Indonesia, 2024)
This study aims to describe the use of media made from natural leaves to improve classification skills in children aged 5-6 years at the Pelangi Saran Integrated PAUD, Belimbing District, Melawi Regency. The research method used is descriptive method in the form of action research. The subjects in this study were early childhood in group B. The research location was in Belimbing District, Melawi District, PAUD Terpadu Pelangi Saran. Data collection techniques used in this study were observation, interviews and documentation. The results of the study show that, The planning is carried out, namely preparing research instruments and Daily Learning Implementation Plans (RPPH) in the use of media made from natural leaves to develop classification skills, making a schedule for implementing learning, preparing media made from natural leaves to be used in learning activities. The implementation of this research was carried out through three cycles, using media made from natural leaves, carried out inside and outside the classroom. There was an increase from the three cycles with the use of media made from natural leaves to improve the classification abilities of children aged 5-6 at the Pelangi Saran Integrated PAUD, Belimbing District. Thus the use of media made from natural leaves to improve classification skills in children aged 5-6 years at the Pelangi Saran Integrated PAUD in Belimbing District has been well implemented